2013
DOI: 10.1186/1471-2334-13-441
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of influenza vaccine against laboratory-confirmed influenza, in the late 2011–2012 season in Spain, among population targeted for vaccination

Abstract: BackgroundIn Spain, the influenza vaccine effectiveness (VE) was estimated in the last three seasons using the observational study cycEVA conducted in the frame of the existing Spanish Influenza Sentinel Surveillance System. The objective of the study was to estimate influenza vaccine effectiveness (VE) against medically attended, laboratory-confirmed influenza-like illness (ILI) among the target groups for vaccination in Spain in the 2011–2012 season. We also studied influenza VE in the early (weeks 52/2011-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 38 publications
(50 reference statements)
1
27
1
3
Order By: Relevance
“…Durante la fase piloto 2008-09 16 se demostró la viabilidad del estudio siendo una etapa crucial para afrontar el reto que supuso la estimación de la efectividad de la vacuna estacional 2009-10 y la monovalente pandémica durante la pandemia de 2009 18 . Posteriormente el estudio cycEVA se consolidó a lo largo de las tres ediciones post-pandémicas [19][20][21][22] .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Durante la fase piloto 2008-09 16 se demostró la viabilidad del estudio siendo una etapa crucial para afrontar el reto que supuso la estimación de la efectividad de la vacuna estacional 2009-10 y la monovalente pandémica durante la pandemia de 2009 18 . Posteriormente el estudio cycEVA se consolidó a lo largo de las tres ediciones post-pandémicas [19][20][21][22] .…”
Section: Discussionunclassified
“…A partir de la edición 2009-10 se recogió información sobre los dos nuevos factores de riesgo de complicaciones por gripe descritos en la pandemia de 2009, embarazo y obesidad mórbida (IMC≥40 kg/m 2 ). Gracias a la incorporación de la variable "pertenencia a los grupos recomendados de vacunación", desde la edición 2010-11 se obtuvieron estimaciones de EV antigripal en España para los grupos diana de vacunación [20][21] . La inclusión de la variable "número de consultas al MP en los últimos 12 meses" permite ajustar las estimaciones de EV por la conducta de frecuentación médica (health seeking behavior) de los pacientes incluidos en el estudio 28 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Yearly revaccination is necessary because circulating strains and/or vaccine composition change every influenza season. Additionally, previous studies have found that influenza vaccine effectiveness (VE) declines over time since vaccination in some populations does not provide significant protection in most cases after 90-120 days [3][4][5][6][7]. Many factors impact VE estimates and speed of decline -including age, comorbidities, herd immunity, use of adjuvants, type of vaccine administered (live attenuated or inactivated), prior natural influenza exposure, prior influenza vaccination, antigenic drift, and study design [6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have assessed influenza VE declines in relatively small sample sizes or from 1 influenza season [3][4][5][6]14]. Additionally, many of these studies have been conducted outside the United States, in regions that have different vaccine composition (adjuvant vs. non-adjuvanted) [6,15], and vaccine recommendations [2,16], and may also have differences in circulating strains and in the proportion of LAIV vs. IIV and quadrivalent versus trivalent vaccine which is administered.…”
Section: Introductionmentioning
confidence: 99%